Pageblug: Tinjauan Aspek Antropologis untuk Mendukung Penerapan Protokol Kesehatan dalam Menghadapi Covid-19 di Jawa Tengah - Eko Punto Hendro (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
Pageblug or outbreaks that occur in the community such as the pandemic of the current Covid-19 virus, have actually existed since time immemorial. This series of Pageblug events in the past has also provided experience, lessons and at the same time a warning to the community about deviant behaviors for the authorities and society. The method used in this research is descriptive analytical method which is based on observations and interviews. With the occurrence of the covid-19 virus pandemic, it is seen by the Javanese people as the Pageblug event, a natural event that marks that leaders, rulers and people in Central Java must improve their behavior to reach civil society. The leaders or rulers or officials must be able to provide protection and exemplary for the community, and on the other hand the people or society will also obey all orders given by the leader or the ruler.